Unexpected role for Helicobacter pylori DNA polymerase I as a source of genetic variability. - María-Victoria García-Ortíz; Stéphanie Marsin; Mercedes E Arana; Didier Gasparutto; Raphaël Guérois; Thomas A Kunkel; J Pablo Radicella (PLoS Genetics)
Helicobacter pylori, a human pathogen infecting about half of the world population, is characterised by its large intraspecies variability. Its genome plasticity has been invoked as the basis for its high adaptation capacity. Consistent with its small genome, H. pylori possesses only two bona fide DNA polymerases, Pol I and the replicative Pol III, lacking homologues of translesion synthesis DNA polymerases. Bacterial DNA polymerases I are implicated both in normal DNA replication and in DNA repair. We report that H. pylori DNA Pol I 5'- 3' exonuclease domain is essential for viability, probably through its involvement in DNA replication. We show here that, despite the fact that it also plays crucial roles in DNA repair, Pol I contributes to genomic instability. Indeed, strains defective in the DNA polymerase activity of the protein, although sensitive to genotoxic agents, display reduced mutation frequencies. Conversely, overexpression of Pol I leads to a hypermutator phenotype. Although the purified protein displays an intrinsic fidelity during replication of undamaged DNA, it lacks a proofreading activity, allowing it to efficiently elongate mismatched primers and perform mutagenic translesion synthesis. In agreement with this finding, we show that the spontaneous mutator phenotype of a strain deficient in the removal of oxidised pyrimidines from the genome is in part dependent on the presence of an active DNA Pol I. This study provides evidence for an unexpected role of DNA polymerase I in generating genomic plasticity.